Konsep Bersih Mandiri: Strategi Pengelolaan Sampah Terpadu Berbasis Masyarakat Untuk Mewujudkan SDGs - Jaenudin, Dadang; Retnowati, Rita; Falih Setyonegoro, Murfid (KENDURI : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2023)
The waste problem must be addressed collaboratively by the government and the community itself. Therefore, a strategy is needed specifically in waste management to create a clean and environmentally friendly residential environment. The lack of awareness of waste management leads to social, economic, and environmental problems. Community-based management is a solution to educate community members and develop sustainable initiatives to improve waste management practices. The involvement of students, youth, and local communities in environmental issues is an effective tool to overcome waste management challenges, but to be sustainable, mentoring from all parties is needed to provide support and commitment. Therefore, a community-based strategy is needed in the concept of clean independence for the priority of household solid waste management that can be implemented in Pelayangan District. The purpose of this study is to realize sustainable development through a community-based waste management strategy in Palayangan District, Jambi City. The urgency of this research is to solve the waste problem in Palayangan District, Jambi, analyzing at which point of the waste disposal chain can be improved and perfected so that the waste that enters the landfill is ultimately only waste that cannot be truly processed again with the hope that it will ultimately determine the success in overcoming the waste problem in Indonesia in order to realize the SDGs. The method used in this research is a mix method approach. Data sources in this research are divided into two types, namely respondents and informants. Respondents are used to identify factors that influence household solid waste management are residents in Pelayangan District, analyzing community involvement in household solid waste management is the population. Informants are used to assist in the preparation of the SWOT analysis design to obtain the strengths, weaknesses, opportunities, and threats of household solid waste management in Pelayangan District. The mandatory output of this research is 1 article published in the Journal of Natural Resources and Environmental Management and HAKI.